CLEC5a-directed bispecific antibody for effective cellular phagocytosis - Vivekananda Kedage; Diego Ellerman; Mingjian Fei; Wei-Ching Liang; Gu Zhang; Eric Cheng; Juan Zhang; Yongmei Chen; Haochu Huang; Wyne P. Lee; Yan Wu; Minhong Yan (Taylor & Francis Group, 2022)
While antibody-dependent cellular phagocytosis mediated by activating Fcγ receptor is a key mechanism underlying many antibody drugs, their full therapeutic activities can be restricted by the inhibitory Fcγ receptor IIB (FcγRIIB). Here, we describe a bispecific antibody approach that harnesses phagocytic receptor CLEC5A (C-type Lectin Domain Containing 5A) to drive Fcγ receptor-independent phagocytosis, potentially circumventing the negative impact of FcγRIIB. First, we established the effectiveness of such an approach by constructing bispecific antibodies that simultaneously target CLEC5A and live B cells. Furthermore, we demonstrated its in vivo application for regulatory T cell depletion and subsequent tumor regression.